대추 열수 추출물을 첨가한 호상 요구르트의 품질 특성 - 김안나(An-Na Kim); 정현아(Hyeon-A Jung) (東아시아食生活學會誌, 2013)
Jujube is a functional food, containing medicinal ingredients without side effects. Jujube can relieve digestive upset, inhibit tumor growth and protect the liver. It includes sterols, alkaloids, saponins, vitamins, organic acids, and amino acids. Jujube has also received attention as an anticancer agent and as a diet food. However, it is rare to find yogurt made with jujube, so we considered adding jujube powder to yogurt to popularize it as a new health food. We made yogurt with jujube powder at 0, 1, 2, 3, and 4%. We measured pH, acidity, color properties (brightness, redness, yellowness), viscosity, sensory qualities (color, flavor, taste, overall quality). We also experimented with storage stability at intervals of 1, 5, 10, 15, and 20 days. The results showed that pH increased significantly (p<0.001) with increasing amounts of added jujube powder. The pH also rose significantly with longer storage, but tended to decrease after 20 days. Acidity was reduced during the storage period. Viscosity was highest with 1% added jujube powder (p<0.001) on day 5 of storage (p<0.001). The L color value decreased as the amount of added jujube powder increased, whereas the a-value (redness) and b-value (yellowness) increased (p<0.001). In an sensory test, color in samples with 0, 1, and 2% jujube powder exhibited the highest values (p<0.01), but no significant differences in flavor or texture were observed. Sweetness and sourness were highest in the yogurt with 3% jujube powder (p<0.05). Overall quality tended to be higher for yogurt with 3% jujube powder, but the difference was in significant. Taken together, our results indicate that yogurt with 3% jujube powder may the most suitable for manufacturing purposes.